Real‐Time Monitoring of Hydrogen Production by Water Electrolysis Using a Tapered Polarization‐Maintaining Optical Fiber Mach–Zehnder Interferometer. Issue 10 (2nd August 2022) - Wan, Hao; Long, Gang; Yang, Siyuan; Niu, Kunpeng; Lyu, Dajuan; Liao, Zhaolong; Shui, Biao; Zhou, Ai; Wang, Ning
Abstract : Gas microbubbles easily cover surface active sites of the solid electrodes in most gas evolution reactions, hindering the transfer of mass and energy and declining the reaction efficiency. However, online monitoring of gas bubbles' behaviors on the surface of solid electrodes accurately in real time remains challenging. Herein, a tapered polarization‐maintaining fiber Mach–Zehnder interferometer for in situ monitoring of H2 bubbles detachment in water electrolysis is reported. In the experiment, the H2 bubble released from the platinum microelectrode can be detected by recording the variation of transmitted optical power in the optical fiber. By comparing it with the electrochemical measurement and the charge‐coupled device imaging, the measurement accuracy can be regarded as near 100%, and the time resolution is determined to be ≈ms. It is found that the size of the detached bubbles on the microelectrode surface is positively correlated with the electrolysis voltage. The increasing electrolysis time causes a long detachment time. Three different charged surfactants are all proved to accelerate the H2 detachment. This method is adapted to study gas bubble behaviors in various complex gas‐involving reaction systems, even for the invisible gas bubbles in a dark environment. Abstract : Herein, a tapered polarization‐maintaining fiber Mach–Zehnder interferometer for in situ monitoring of H2 bubble detachment in water electrolysis is reported, which exhibits great accuracy and time resolution, and is adapted to study gas bubble behaviors in various complex gas‐involving reaction systems, even for invisible gas bubbles in a dark environment.